Heat-insulating and weather-resistant composite material, preparation method and application of heat-insulating and weather-resistant composite material to car cover

By adopting a three-layer heat-insulating and weather-resistant composite material, using the combination of modified polyacrylonitrile, EPE foam cotton sheet and PP non-woven fabric, the problem of insufficient thermal insulation and weather-resistant performance of existing car clothing materials is solved, and higher thermal insulation and weather-resistant performance are achieved and service life is extended.

CN119590057AActive Publication Date: 2025-03-11WUHAN KEYIJIE TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411769669.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-11
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

The existing car clothing materials have shortcomings in thermal insulation and weather resistance, which leads to prone to aging and damage when used in open-air environments and short service life.

Method used

It adopts a three-layer structure heat-insulating and weather-resistant composite material. The outer layer film is made of modified polyacrylonitrile by electrospinning. The intermediate layer film is EPE foam cotton sheet and the inner layer film is PP non-woven fabric. It is bonded by pressure-sensitive adhesive to improve the thermal insulation and weather-resistant properties of the material.

Benefits of technology

It significantly improves the thermal insulation and weather resistance of car clothing materials, extends its service life, and can better resist the influence of dust, dirt, rain, snow and ultraviolet rays.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119590057A_ABST
    Figure CN119590057A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of layered composite materials, in particular to a heat-insulating and weather-resistant composite material, a preparation method and application of the heat-insulating and weather-resistant composite material to car clothing. The composite material comprises a three-layer structure including an outer layer film, a middle layer film and an inner layer film, the inner layer film is a PP non-woven fabric, the material is soft, vehicle paint cannot be damaged due to friction, the middle layer film is an EPE foam cotton piece, the heat conductivity coefficient of air in a pore structure contained in the middle layer film is low, the heat insulation effect is good, and the heat insulation effect is good. The outer-layer film is prepared from polyacrylonitrile as a main raw material through electrostatic spinning; polyacrylonitrile has good weather resistance and solarization resistance, polyacrylonitrile is subjected to modification treatment, a waterproof component and an anti-ultraviolet component are introduced, and the anti-ultraviolet performance and the waterproof performance can be improved; a heat insulation component and an anti-oxidation component are added into the modified polyacrylonitrile spinning solution, so that the heat insulation performance and the anti-oxidation performance of the outer layer film can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of layered composite materials, and in particular to a heat-insulating and weather-resistant composite material, a preparation method and application thereof in car covers. Background Art

[0002] When a car is parked in an open-air environment, it is easily affected by dust, dirt, rain, snow, ultraviolet rays, etc., which in turn affects the use of the car. Therefore, it is generally necessary to use a car cover to protect the car. When a car cover is exposed to the open air for a long time, it is easy to age and break, and its service life is short. Therefore, the weather resistance of the material used to make the car cover is required to be high. In addition, in order to prevent the temperature inside the car from being too high under sunlight, the car cover material is also required to have good thermal insulation performance.

[0003] Chinese patent CN117301677B discloses a heat-insulating flame-retardant car cover of polyurethane layered material, wherein the car cover is composed of a first polyurethane layer, a second polyurethane layer and a fiber layer bonded by an adhesive, and the polyurethane layer contains a heat-insulating flame retardant, which is prepared by montmorillonite and aluminum chloride. However, the heat-insulating flame retardant is an inorganic composite particle, and has poor compatibility and dispersion uniformity in polyurethane, and insufficient heat-insulating performance. In addition, the weather resistance of the car cover needs to be improved. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides a heat-insulating and weather-resistant composite material to solve the problem of poor heat-insulating and weather-resistant performance of car covers in the prior art.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0006] A method for preparing a heat-insulating and weather-resistant composite material comprises the following steps:

[0007] Step 1, adding polyacrylonitrile resin to N,N-dimethylformamide, stirring until dissolved, adding hexafluorobutyl acrylate, 4-propyleneoxy-2-hydroxybenzophenone and benzoyl peroxide, reacting, and after the reaction is completed, precipitating, filtering, washing, and drying to obtain modified polyacrylonitrile;

[0008] Step 2: Add modified polyacrylonitrile to N,N-dimethylformamide, stir until dissolved, add epoxy-modified montmorillonite, epoxy-modified silver powder and N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine, continue to react, and after the reaction is completed, obtain a reaction solution, electrospin the reaction solution, dry it, and roll it to obtain a modified polyacrylonitrile fiber membrane;

[0009] Step 3: Use modified polyacrylonitrile fiber film as the outer film, EPE (Expandable Polyethylene) foam cotton sheet as the middle film, and PP non-woven fabric as the inner film, and bond the outer film, the middle film and the inner film with a pressure-sensitive adhesive to obtain a heat-insulating and weather-resistant composite material.

[0010] Preferably, in the step 1, the mass ratio of polyacrylonitrile resin, N,N-dimethylformamide, hexafluorobutyl acrylate, 4-propyleneoxy-2-hydroxybenzophenone and benzoyl peroxide is 100:(800-1000):(2.5-5):(3.5-6):(0.05-0.1).

[0011] Preferably, in the step 1, the stirring conditions are stirring at a stirring speed of 100-200 r / min and a temperature of 50-70° C., and the reaction conditions are reacting at a temperature of 80-90° C. for 1.5-2.5 h.

[0012] Preferably, in the step 2, the mass ratio of modified polyacrylonitrile, N,N-dimethylformamide, epoxy-modified montmorillonite, epoxy-modified silver powder and N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine is 100:(800-1000):(0.5-1):(1-2):(4-5).

[0013] Preferably, in the step 2, the stirring conditions are stirring at a stirring speed of 100-200 r / min and a temperature of 50-70°C, and the conditions for continuing the reaction are stirring at a stirring speed of 100-200 r / min and a temperature of 75-85°C for 30-40 hours.

[0014] Preferably, in the step 2, during electrospinning, the spinning voltage is 28 kV, the flow rate is 0.5 mL / h, and the receiving distance is 15 cm.

[0015] Preferably, the epoxy-modified montmorillonite in step 2 is prepared by the following steps:

[0016] The pH value of the ethanol aqueous solution is adjusted to 3.5-4.5, γ-glycidyloxypropyltrimethoxysilane is added, and after hydrolysis, montmorillonite is added to react. After the reaction is completed, the reaction is filtered, washed, and dried to obtain epoxy-modified montmorillonite.

[0017] Preferably, the mass ratio of the ethanol aqueous solution, γ-glycidyloxypropyltrimethoxysilane and montmorillonite is 100:2.5:(2.5-4), the hydrolysis conditions are hydrolysis at a stirring speed of 100-200 r / min for 3.5-4.5 h, and the reaction conditions are reflux reaction at a temperature of 65-75° C. for 20-30 h.

[0018] Preferably, the ethanol aqueous solution is a 90 wt % ethanol aqueous solution.

[0019] Preferably, the epoxy-modified silver powder in step 2 is prepared by the following steps:

[0020] The mixed solvent is mixed with γ-glycidyloxypropyltrimethoxysilane, the pH value is adjusted to 4-6, silver powder is added, and the reaction is carried out. After the reaction is completed, the reaction is filtered, washed, and dried to obtain epoxy-modified silver powder.

[0021] Preferably, the mixed solvent is formed by mixing ethyl acetate / butyl acetate / cyclohexanone in a mass ratio of 2:1:1, the mass ratio of the mixed solvent, γ-glycidyloxypropyltrimethoxysilane and silver powder is 100:1:(1-2), and the reaction conditions are to react at a temperature of 50-70°C for 8-10h.

[0022] The invention also discloses a heat-insulating and weather-resistant composite material prepared by adopting the preparation method of the heat-insulating and weather-resistant composite material as mentioned above.

[0023] Preferably, the heat-insulating and weather-resistant composite material as described above is used in car covers.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] The composite material of the present invention comprises a three-layer structure of an outer film, an intermediate film and an inner film, wherein the inner film is a PP non-woven fabric, which is soft and will not damage the car paint due to friction, the intermediate film is an EPE foam cotton sheet, the air thermal conductivity in the pore structure contained in the intermediate film is low, and the heat insulation effect is good, and the outer film is made of polyacrylonitrile as the main raw material through electrostatic spinning; polyacrylonitrile has good weather resistance and sunlight resistance, and polyacrylonitrile is modified to introduce waterproof components and anti-ultraviolet components, which can improve the anti-ultraviolet performance and waterproof performance; heat insulation components and antioxidant components are added to the modified polyacrylonitrile spinning solution, which can improve the heat insulation performance and antioxidant performance of the outer film; under the action of the antioxidant and the anti-ultraviolet component, the outer film has good anti-aging performance and high weather resistance;

[0026] During the polyacrylonitrile modification process, under the action of the initiator, the waterproof component hexafluorobutyl acrylate and the anti-ultraviolet component 4-propyleneoxy-2-hydroxybenzophenone are grafted onto the polyacrylonitrile molecular chain. The waterproof component and the anti-ultraviolet component have high compatibility and uniform dispersion in the polyacrylonitrile, and have good anti-ultraviolet and waterproof properties.

[0027] The antioxidant is N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl) hexamethylenediamine, which has strong antioxidant properties and good stability. Its molecular chain can be entangled with the polyacrylonitrile molecular chain. The thermal insulation components are montmorillonite and silver powder. Montmorillonite has a lamellar thermal insulation effect, and the silver powder has a high reflectivity and can reflect heat away. Both have good thermal insulation properties. Montmorillonite and silver powder are epoxy-modified. Through the epoxy group and N,N'-bis-(3-(3,5-di-tert-butyl-4- By the ring-opening reaction of the imino group on the N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine molecule, the montmorillonite and the silver powder are connected to the N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine molecule through a stable chemical bond, and then the compatibility and dispersion uniformity of the montmorillonite and the silver powder in the modified polyacrylonitrile spinning solution are improved through the mutual entanglement between the N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine and the polyacrylonitrile molecular chain, and the thermal insulation performance is enhanced.

[0028] Figure 1 This is a process flow chart for preparing the heat-insulating and weather-resistant composite material of the present invention;

[0029] Figure 2 A bar chart showing the test results of thermal insulation performance of modified polyacrylonitrile fiber membranes prepared in Examples 1-6 of the present invention and Comparative Examples 1-2;

[0030] Figure 3 It is a bar chart showing the test results of the anti-ultraviolet aging performance of the modified polyacrylonitrile fiber membranes prepared in Examples 1-6 of the present invention and Comparative Examples 1-2. DETAILED DESCRIPTION

[0031] Example 1

[0032] This embodiment discloses a method for preparing a heat-insulating and weather-resistant composite material, comprising the following steps:

[0033] Step 1, adding polyacrylonitrile resin to N,N-dimethylformamide, stirring at a stirring speed of 100r / min and a temperature of 70°C until dissolved, adding hexafluorobutyl acrylate, 4-propyleneoxy-2-hydroxybenzophenone and benzoyl peroxide, the mass ratio of polyacrylonitrile resin, N,N-dimethylformamide, hexafluorobutyl acrylate, 4-propyleneoxy-2-hydroxybenzophenone, and benzoyl peroxide is 100:800:2.5:3.5:0.05, reacting at a temperature of 80°C for 2.5h, after the reaction is completed, adding ethanol 3 times the mass of N,N-dimethylformamide for precipitation, filtering, washing with ethanol 3 times, and drying in a 50°C vacuum drying oven for 20h to obtain modified polyacrylonitrile;

[0034] Step 2: Add modified polyacrylonitrile to N,N-dimethylformamide, stir at a stirring speed of 100 r / min and a temperature of 70°C until dissolved, add epoxy-modified montmorillonite, epoxy-modified silver powder and N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine, modified polyacrylonitrile, N,N-dimethylformamide, epoxy-modified montmorillonite, epoxy-modified silver powder and N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine, The mass ratio of hydroxyphenyl)propionyl)hexamethylenediamine is 100:800:0.5:1:4, and the reaction is carried out at a stirring speed of 100r / min and a temperature of 75°C for 40h. After the reaction is completed, a reaction liquid is obtained, and the reaction liquid is subjected to electrostatic spinning at a spinning voltage of 28kV, a flow rate of 0.5mL / h, and a receiving distance of 15cm. The reaction liquid is placed in a vacuum drying oven at 60°C and dried for 12h, and rolled at a pressure of 5MPa for 2min to obtain a modified polyacrylonitrile fiber membrane;

[0035] The thickness of the modified polyacrylonitrile fiber membrane is 50 μm;

[0036] Wherein, the epoxy modified montmorillonite is prepared by the following steps:

[0037] The pH value of the 90wt% ethanol aqueous solution was adjusted to 3.5 with a 1wt% acetic acid aqueous solution, γ-glycidyloxypropyltrimethoxysilane was added, and hydrolysis was carried out at a stirring speed of 100r / min for 4.5h, and montmorillonite was added, and the mass ratio of the 90wt% ethanol aqueous solution, γ-glycidyloxypropyltrimethoxysilane, and montmorillonite was 100:2.5:2.5, and refluxed at 65°C for 30h. After the reaction was completed, the mixture was filtered, washed with ethanol 3 times, and dried in a vacuum drying oven at 50°C for 20h to obtain epoxy-modified montmorillonite;

[0038] The epoxy modified silver powder is prepared by the following steps:

[0039] The mixed solvent was mixed with γ-glycidyloxypropyltrimethoxysilane, the pH value was adjusted to 4 with 1wt% acetic acid aqueous solution, silver powder was added, the mass ratio of the mixed solvent, γ-glycidyloxypropyltrimethoxysilane and silver powder was 100:1:1, and the mixture was reacted at 50°C for 10h. After the reaction was completed, the mixture was filtered, washed with ethanol for 3 times, and dried in a vacuum drying oven at 50°C for 20h to obtain epoxy-modified silver powder;

[0040] The mixed solvent is prepared by mixing ethyl acetate / butyl acetate / cyclohexanone in a mass ratio of 2:1:1;

[0041] Step 3: Use modified polyacrylonitrile fiber film as the outer film, EPE foam cotton sheet as the middle film, PP non-woven fabric as the inner film, and bond the outer film, the middle film and the inner film with a pressure-sensitive adhesive to obtain a heat-insulating and weather-resistant composite material.

[0042] Example 2

[0043] This embodiment discloses a method for preparing a heat-insulating and weather-resistant composite material, comprising the following steps:

[0044] Step 1, adding polyacrylonitrile resin to N,N-dimethylformamide, stirring at a stirring speed of 200r / min and a temperature of 50°C until dissolved, adding hexafluorobutyl acrylate, 4-propyleneoxy-2-hydroxybenzophenone and benzoyl peroxide, the mass ratio of polyacrylonitrile resin, N,N-dimethylformamide, hexafluorobutyl acrylate, 4-propyleneoxy-2-hydroxybenzophenone, and benzoyl peroxide is 100:1000:5:6:0.1, reacting at a temperature of 90°C for 1.5h, after the reaction is completed, adding ethanol 3 times the mass of N,N-dimethylformamide for precipitation, filtering, washing with ethanol 3 times, and drying in a 50°C vacuum drying oven for 20h to obtain modified polyacrylonitrile;

[0045] Step 2: Add modified polyacrylonitrile to N,N-dimethylformamide, stir at a stirring speed of 200r / min and a temperature of 50°C until dissolved, add epoxy-modified montmorillonite, epoxy-modified silver powder and N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine, modified polyacrylonitrile, N,N-dimethylformamide, epoxy-modified montmorillonite, epoxy-modified silver powder and N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine, The mass ratio of hydroxyphenyl)propionyl)hexamethylenediamine is 100:1000:1:2:5, and the reaction is carried out at a stirring speed of 200r / min and a temperature of 85°C for 30h. After the reaction is completed, a reaction liquid is obtained, and the reaction liquid is subjected to electrostatic spinning at a spinning voltage of 28kV, a flow rate of 0.5mL / h, and a receiving distance of 15cm. The reaction liquid is placed in a vacuum drying oven at 60°C and dried for 12h, and rolled at a pressure of 5MPa for 2min to obtain a modified polyacrylonitrile fiber membrane;

[0046] The thickness of the modified polyacrylonitrile fiber membrane is 50 μm;

[0047] Wherein, the epoxy modified montmorillonite is prepared by the following steps:

[0048] The pH value of the 90wt% ethanol aqueous solution was adjusted to 4.5 with a 1wt% acetic acid aqueous solution, γ-glycidyloxypropyltrimethoxysilane was added, and hydrolysis was carried out at a stirring speed of 200r / min for 3.5h, and montmorillonite was added, and the mass ratio of the 90wt% ethanol aqueous solution, γ-glycidyloxypropyltrimethoxysilane, and montmorillonite was 100:2.5:4, and refluxed at 75°C for 20h. After the reaction was completed, the mixture was filtered, washed with ethanol 3 times, and dried in a vacuum drying oven at 50°C for 20h to obtain epoxy-modified montmorillonite;

[0049] The epoxy modified silver powder is prepared by the following steps:

[0050] The mixed solvent was mixed with γ-glycidyloxypropyltrimethoxysilane, the pH value was adjusted to 6 with 1wt% acetic acid aqueous solution, silver powder was added, the mass ratio of the mixed solvent, γ-glycidyloxypropyltrimethoxysilane and silver powder was 100:1:2, and the mixture was reacted at 70°C for 8h. After the reaction was completed, the mixture was filtered, washed with ethanol for 3 times, and dried in a vacuum drying oven at 50°C for 20h to obtain epoxy-modified silver powder;

[0051] The mixed solvent is prepared by mixing ethyl acetate / butyl acetate / cyclohexanone in a mass ratio of 2:1:1;

[0052] Step 3: Use modified polyacrylonitrile fiber film as the outer film, EPE foam cotton sheet as the middle film, PP non-woven fabric as the inner film, and bond the outer film, the middle film and the inner film with a pressure-sensitive adhesive to obtain a heat-insulating and weather-resistant composite material.

[0053] Example 3

[0054] This embodiment discloses a method for preparing a heat-insulating and weather-resistant composite material, comprising the following steps:

[0055] Step 1, adding polyacrylonitrile resin to N,N-dimethylformamide, stirring at a stirring speed of 150r / min and a temperature of 60°C until dissolved, adding hexafluorobutyl acrylate, 4-propyleneoxy-2-hydroxybenzophenone and benzoyl peroxide, the mass ratio of polyacrylonitrile resin, N,N-dimethylformamide, hexafluorobutyl acrylate, 4-propyleneoxy-2-hydroxybenzophenone, and benzoyl peroxide is 100:840:3:4:0.06, reacting at a temperature of 85°C for 2h, after the reaction is completed, adding ethanol 3 times the mass of N,N-dimethylformamide for precipitation, filtering, washing with ethanol 3 times, and drying in a 50°C vacuum drying oven for 20h to obtain modified polyacrylonitrile;

[0056] Step 2: Add modified polyacrylonitrile to N,N-dimethylformamide, stir at a stirring speed of 150r / min and a temperature of 60°C until dissolved, add epoxy-modified montmorillonite, epoxy-modified silver powder and N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine, modified polyacrylonitrile, N,N-dimethylformamide, epoxy-modified montmorillonite, epoxy-modified silver powder and N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine The mass ratio of phenyl) propionyl) hexamethylenediamine is 100:840:0.6:1.2:4.2, and the reaction is carried out at a stirring speed of 150r / min and a temperature of 80°C for 36h. After the reaction is completed, a reaction liquid is obtained, and the reaction liquid is subjected to electrostatic spinning at a spinning voltage of 28kV, a flow rate of 0.5mL / h, and a receiving distance of 15cm. The reaction liquid is placed in a vacuum drying oven at 60°C and dried for 12h, and rolled at a pressure of 5MPa for 2min to obtain a modified polyacrylonitrile fiber membrane;

[0057] The thickness of the modified polyacrylonitrile fiber membrane is 50 μm;

[0058] Wherein, the epoxy modified montmorillonite is prepared by the following steps:

[0059] The pH value of the 90wt% ethanol aqueous solution was adjusted to 4 with a 1wt% acetic acid aqueous solution, γ-glycidyloxypropyltrimethoxysilane was added, and hydrolysis was carried out at a stirring speed of 150r / min for 4h, and montmorillonite was added, and the mass ratio of the 90wt% ethanol aqueous solution, γ-glycidyloxypropyltrimethoxysilane, and montmorillonite was 100:2.5:2.8, and refluxed at 70°C for 24h. After the reaction was completed, the mixture was filtered, washed with ethanol for 3 times, and dried in a vacuum drying oven at 50°C for 20h to obtain epoxy-modified montmorillonite;

[0060] The epoxy modified silver powder is prepared by the following steps:

[0061] The mixed solvent was mixed with γ-glycidyloxypropyltrimethoxysilane, the pH value was adjusted to 5 with 1wt% acetic acid aqueous solution, silver powder was added, the mass ratio of the mixed solvent, γ-glycidyloxypropyltrimethoxysilane and silver powder was 100:1:1.2, and the mixture was reacted at 60°C for 9h. After the reaction was completed, the mixture was filtered, washed with ethanol for 3 times, and dried in a vacuum drying oven at 50°C for 20h to obtain epoxy-modified silver powder;

[0062] The mixed solvent is prepared by mixing ethyl acetate / butyl acetate / cyclohexanone in a mass ratio of 2:1:1;

[0063] Step 3: Use modified polyacrylonitrile fiber film as the outer film, EPE foam cotton sheet as the middle film, PP non-woven fabric as the inner film, and bond the outer film, the middle film and the inner film with a pressure-sensitive adhesive to obtain a heat-insulating and weather-resistant composite material.

[0064] Example 4

[0065] This embodiment discloses a method for preparing a heat-insulating and weather-resistant composite material, comprising the following steps:

[0066] Step 1, adding polyacrylonitrile resin to N,N-dimethylformamide, stirring at a stirring speed of 150r / min and a temperature of 60°C until dissolved, adding hexafluorobutyl acrylate, 4-propyleneoxy-2-hydroxybenzophenone and benzoyl peroxide, the mass ratio of polyacrylonitrile resin, N,N-dimethylformamide, hexafluorobutyl acrylate, 4-propyleneoxy-2-hydroxybenzophenone, and benzoyl peroxide is 100:880:3.5:4.5:0.07, reacting at a temperature of 85°C for 2h, after the reaction is completed, adding ethanol 3 times the mass of N,N-dimethylformamide for precipitation, filtering, washing with ethanol 3 times, and drying in a 50°C vacuum drying oven for 20h to obtain modified polyacrylonitrile;

[0067] Step 2: Add modified polyacrylonitrile to N,N-dimethylformamide, stir at a stirring speed of 150r / min and a temperature of 60°C until dissolved, add epoxy-modified montmorillonite, epoxy-modified silver powder and N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine, modified polyacrylonitrile, N,N-dimethylformamide, epoxy-modified montmorillonite, epoxy-modified silver powder and N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine The mass ratio of phenyl)propionyl)hexamethylenediamine is 100:880:0.7:1.4:4.4, and the reaction is carried out at a stirring speed of 150r / min and a temperature of 80°C for 36h. After the reaction is completed, a reaction liquid is obtained, and the reaction liquid is subjected to electrostatic spinning at a spinning voltage of 28kV, a flow rate of 0.5mL / h, and a receiving distance of 15cm. The reaction liquid is placed in a vacuum drying oven at 60°C and dried for 12h, and rolled at a pressure of 5MPa for 2min to obtain a modified polyacrylonitrile fiber membrane;

[0068] The thickness of the modified polyacrylonitrile fiber membrane is 50 μm;

[0069] Wherein, the epoxy modified montmorillonite is prepared by the following steps:

[0070] The pH value of the 90wt% ethanol aqueous solution was adjusted to 4 with a 1wt% acetic acid aqueous solution, γ-glycidyloxypropyltrimethoxysilane was added, and hydrolysis was carried out at a stirring speed of 150r / min for 4h, and montmorillonite was added, and the mass ratio of the 90wt% ethanol aqueous solution, γ-glycidyloxypropyltrimethoxysilane, and montmorillonite was 100:2.5:3.1, and refluxed at 70°C for 24h. After the reaction was completed, the mixture was filtered, washed with ethanol 3 times, and dried in a vacuum drying oven at 50°C for 20h to obtain epoxy-modified montmorillonite;

[0071] The epoxy modified silver powder is prepared by the following steps:

[0072] The mixed solvent was mixed with γ-glycidyloxypropyltrimethoxysilane, the pH value was adjusted to 5 with 1wt% acetic acid aqueous solution, silver powder was added, the mass ratio of the mixed solvent, γ-glycidyloxypropyltrimethoxysilane and silver powder was 100:1:1.4, and the mixture was reacted at 60°C for 9h. After the reaction was completed, the mixture was filtered, washed with ethanol for 3 times, and dried in a vacuum drying oven at 50°C for 20h to obtain epoxy-modified silver powder;

[0073] The mixed solvent is prepared by mixing ethyl acetate / butyl acetate / cyclohexanone in a mass ratio of 2:1:1;

[0074] Step 3: Use modified polyacrylonitrile fiber film as the outer film, EPE foam cotton sheet as the middle film, PP non-woven fabric as the inner film, and bond the outer film, the middle film and the inner film with a pressure-sensitive adhesive to obtain a heat-insulating and weather-resistant composite material.

[0075] Example 5

[0076] This embodiment discloses a method for preparing a heat-insulating and weather-resistant composite material, comprising the following steps:

[0077] Step 1, adding polyacrylonitrile resin to N,N-dimethylformamide, stirring at a stirring speed of 150r / min and a temperature of 60°C until dissolved, adding hexafluorobutyl acrylate, 4-propyleneoxy-2-hydroxybenzophenone and benzoyl peroxide, the mass ratio of polyacrylonitrile resin, N,N-dimethylformamide, hexafluorobutyl acrylate, 4-propyleneoxy-2-hydroxybenzophenone, and benzoyl peroxide is 100:920:4:5:0.08, reacting at a temperature of 85°C for 2h, after the reaction is completed, adding ethanol 3 times the mass of N,N-dimethylformamide for precipitation, filtering, washing with ethanol 3 times, and drying in a 50°C vacuum drying oven for 20h to obtain modified polyacrylonitrile;

[0078] Step 2: Add modified polyacrylonitrile to N,N-dimethylformamide, stir at a stirring speed of 150r / min and a temperature of 60°C until dissolved, add epoxy-modified montmorillonite, epoxy-modified silver powder and N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine, modified polyacrylonitrile, N,N-dimethylformamide, epoxy-modified montmorillonite, epoxy-modified silver powder and N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine The mass ratio of phenyl) propionyl) hexamethylenediamine is 100:920:0.8:1.6:4.6, and the reaction is carried out at a stirring speed of 150r / min and a temperature of 80°C for 36h. After the reaction is completed, a reaction liquid is obtained, and the reaction liquid is subjected to electrostatic spinning at a spinning voltage of 28kV, a flow rate of 0.5mL / h, and a receiving distance of 15cm. The reaction liquid is placed in a vacuum drying oven at 60°C and dried for 12h, and rolled at a pressure of 5MPa for 2min to obtain a modified polyacrylonitrile fiber membrane;

[0079] The thickness of the modified polyacrylonitrile fiber membrane is 50 μm;

[0080] Wherein, the epoxy modified montmorillonite is prepared by the following steps:

[0081] The pH value of the 90wt% ethanol aqueous solution was adjusted to 4 with a 1wt% acetic acid aqueous solution, γ-glycidyloxypropyltrimethoxysilane was added, and hydrolysis was carried out at a stirring speed of 150r / min for 4h, and montmorillonite was added, and the mass ratio of the 90wt% ethanol aqueous solution, γ-glycidyloxypropyltrimethoxysilane, and montmorillonite was 100:2.5:3.4, and refluxed at 70°C for 24h. After the reaction was completed, the mixture was filtered, washed with ethanol 3 times, and dried in a vacuum drying oven at 50°C for 20h to obtain epoxy-modified montmorillonite;

[0082] The epoxy modified silver powder is prepared by the following steps:

[0083] The mixed solvent was mixed with γ-glycidyloxypropyltrimethoxysilane, the pH value was adjusted to 5 with 1wt% acetic acid aqueous solution, silver powder was added, the mass ratio of the mixed solvent, γ-glycidyloxypropyltrimethoxysilane and silver powder was 100:1:1.6, and the mixture was reacted at 60°C for 9h. After the reaction was completed, the mixture was filtered, washed with ethanol for 3 times, and dried in a vacuum drying oven at 50°C for 20h to obtain epoxy-modified silver powder;

[0084] The mixed solvent is prepared by mixing ethyl acetate / butyl acetate / cyclohexanone in a mass ratio of 2:1:1;

[0085] Step 3: Use modified polyacrylonitrile fiber film as the outer film, EPE foam cotton sheet as the middle film, PP non-woven fabric as the inner film, and bond the outer film, the middle film and the inner film with a pressure-sensitive adhesive to obtain a heat-insulating and weather-resistant composite material.

[0086] Example 6

[0087] This embodiment discloses a method for preparing a heat-insulating and weather-resistant composite material, comprising the following steps:

[0088] Step 1, adding polyacrylonitrile resin to N,N-dimethylformamide, stirring at a stirring speed of 150r / min and a temperature of 60°C until dissolved, adding hexafluorobutyl acrylate, 4-propyleneoxy-2-hydroxybenzophenone and benzoyl peroxide, the mass ratio of polyacrylonitrile resin, N,N-dimethylformamide, hexafluorobutyl acrylate, 4-propyleneoxy-2-hydroxybenzophenone, and benzoyl peroxide is 100:960:4.5:5.5:0.09, reacting at a temperature of 85°C for 2h, after the reaction is completed, adding ethanol 3 times the mass of N,N-dimethylformamide for precipitation, filtering, washing with ethanol 3 times, and drying in a 50°C vacuum drying oven for 20h to obtain modified polyacrylonitrile;

[0089] Step 2: Add modified polyacrylonitrile to N,N-dimethylformamide, stir at a stirring speed of 150r / min and a temperature of 60°C until dissolved, add epoxy-modified montmorillonite, epoxy-modified silver powder and N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine, modified polyacrylonitrile, N,N-dimethylformamide, epoxy-modified montmorillonite, epoxy-modified silver powder and N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine The mass ratio of phenyl) propionyl) hexamethylenediamine is 100:960:0.9:1.8:4.8, and the reaction is carried out at a stirring speed of 150r / min and a temperature of 80°C for 36h. After the reaction is completed, a reaction liquid is obtained, and the reaction liquid is subjected to electrostatic spinning at a spinning voltage of 28kV, a flow rate of 0.5mL / h, and a receiving distance of 15cm. The reaction liquid is placed in a vacuum drying oven at 60°C and dried for 12h, and rolled at a pressure of 5MPa for 2min to obtain a modified polyacrylonitrile fiber membrane;

[0090] The thickness of the modified polyacrylonitrile fiber membrane is 50 μm;

[0091] Wherein, the epoxy modified montmorillonite is prepared by the following steps:

[0092] The pH value of the 90wt% ethanol aqueous solution was adjusted to 4 with a 1wt% acetic acid aqueous solution, γ-glycidyloxypropyltrimethoxysilane was added, and hydrolysis was carried out at a stirring speed of 150r / min for 4h, and montmorillonite was added, and the mass ratio of the 90wt% ethanol aqueous solution, γ-glycidyloxypropyltrimethoxysilane, and montmorillonite was 100:2.5:3.7, and refluxed at 70°C for 24h. After the reaction was completed, the mixture was filtered, washed with ethanol 3 times, and dried in a vacuum drying oven at 50°C for 20h to obtain epoxy-modified montmorillonite;

[0093] The epoxy modified silver powder is prepared by the following steps:

[0094] The mixed solvent was mixed with γ-glycidyloxypropyltrimethoxysilane, the pH value was adjusted to 5 with 1wt% acetic acid aqueous solution, silver powder was added, the mass ratio of the mixed solvent, γ-glycidyloxypropyltrimethoxysilane and silver powder was 100:1:1.8, and the mixture was reacted at 60°C for 9h. After the reaction was completed, the mixture was filtered, washed with ethanol for 3 times, and dried in a vacuum drying oven at 50°C for 20h to obtain epoxy-modified silver powder;

[0095] The mixed solvent is prepared by mixing ethyl acetate / butyl acetate / cyclohexanone in a mass ratio of 2:1:1;

[0096] Step 3: Use modified polyacrylonitrile fiber film as the outer film, EPE foam cotton sheet as the middle film, PP non-woven fabric as the inner film, and bond the outer film, the middle film and the inner film with a pressure-sensitive adhesive to obtain a heat-insulating and weather-resistant composite material.

[0097] Comparative Example 1

[0098] This embodiment discloses a method for preparing a heat-insulating and weather-resistant composite material, comprising the following steps:

[0099] Step 1, adding polyacrylonitrile resin to N,N-dimethylformamide, stirring at a stirring speed of 100r / min and a temperature of 70°C until dissolved, adding hexafluorobutyl acrylate and benzoyl peroxide, the mass ratio of polyacrylonitrile resin, N,N-dimethylformamide, hexafluorobutyl acrylate, and benzoyl peroxide is 100:800:2.5:0.05, reacting at a temperature of 80°C for 2.5h, after the reaction is completed, adding ethanol 3 times the mass of N,N-dimethylformamide for precipitation, filtering, washing with ethanol 3 times, and placing in a 50°C vacuum drying oven for drying for 20h to obtain modified polyacrylonitrile;

[0100] Step 2: Add modified polyacrylonitrile to N,N-dimethylformamide, stir at a stirring speed of 100 r / min and a temperature of 70°C until dissolved, add epoxy-modified montmorillonite, epoxy-modified silver powder and N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine, and react at a stirring speed of 100 r / min and a temperature of 75°C for 40 hours. After the reaction is completed, a reaction solution is obtained, 4-propyleneoxy-2-hydroxybenzophenone is added to the reaction solution, and the mixture is stirred to obtain a mixed solution. The mixed solution is subjected to electrostatic spinning at a spinning voltage of 28 kV, a flow rate of 0.5 mL / h, and a receiving distance of 15 cm. The mixture is placed in a vacuum drying oven at 60°C and dried for 12 hours, and rolled at a pressure of 5 MPa for 2 minutes to obtain a modified polyacrylonitrile fiber membrane;

[0101] The thickness of the modified polyacrylonitrile fiber membrane is 50 μm;

[0102] The mass ratio of modified polyacrylonitrile, N,N-dimethylformamide, epoxy-modified montmorillonite, epoxy-modified silver powder, N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine, and 4-propyleneoxy-2-hydroxybenzophenone is 100:800:0.5:1:4:3.3.

[0103] The epoxy modified montmorillonite is prepared by the following steps:

[0104] The pH value of the 90wt% ethanol aqueous solution was adjusted to 3.5 with a 1wt% acetic acid aqueous solution, γ-glycidyloxypropyltrimethoxysilane was added, and hydrolysis was carried out at a stirring speed of 100r / min for 4.5h, and montmorillonite was added, and the mass ratio of the 90wt% ethanol aqueous solution, γ-glycidyloxypropyltrimethoxysilane, and montmorillonite was 100:2.5:2.5, and refluxed at 65°C for 30h. After the reaction was completed, the mixture was filtered, washed with ethanol 3 times, and dried in a vacuum drying oven at 50°C for 20h to obtain epoxy-modified montmorillonite;

[0105] The epoxy modified silver powder is prepared by the following steps:

[0106] The mixed solvent was mixed with γ-glycidyloxypropyltrimethoxysilane, the pH value was adjusted to 4 with 1wt% acetic acid aqueous solution, silver powder was added, the mass ratio of the mixed solvent, γ-glycidyloxypropyltrimethoxysilane and silver powder was 100:1:1, and the mixture was reacted at 50°C for 10h. After the reaction was completed, the mixture was filtered, washed with ethanol for 3 times, and dried in a vacuum drying oven at 50°C for 20h to obtain epoxy-modified silver powder;

[0107] The mixed solvent is prepared by mixing ethyl acetate / butyl acetate / cyclohexanone in a mass ratio of 2:1:1;

[0108] Step 2: Using modified polyacrylonitrile fiber film as the outer film, EPE foam cotton sheet as the middle film, and PP non-woven fabric as the inner film, the outer film, the middle film and the inner film are bonded by pressure-sensitive adhesive to obtain a heat-insulating and weather-resistant composite material.

[0109] Comparative Example 2

[0110] This embodiment discloses a method for preparing a heat-insulating and weather-resistant composite material, comprising the following steps:

[0111] Step 1, adding polyacrylonitrile resin to N,N-dimethylformamide, stirring at a stirring speed of 100r / min and a temperature of 70°C until dissolved, adding hexafluorobutyl acrylate, 4-propyleneoxy-2-hydroxybenzophenone and benzoyl peroxide, the mass ratio of polyacrylonitrile resin, N,N-dimethylformamide, hexafluorobutyl acrylate, 4-propyleneoxy-2-hydroxybenzophenone, and benzoyl peroxide is 100:800:2.5:3.5:0.05, reacting at a temperature of 80°C for 2.5h, after the reaction is completed, adding ethanol 3 times the mass of N,N-dimethylformamide for precipitation, filtering, washing with ethanol 3 times, and drying in a 50°C vacuum drying oven for 20h to obtain modified polyacrylonitrile;

[0112] Step 2: Add modified polyacrylonitrile to N,N-dimethylformamide, stir at a stirring speed of 100 r / min and a temperature of 70°C until dissolved, add montmorillonite, silver powder and N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine, modified polyacrylonitrile, N,N-dimethylformamide, montmorillonite, silver powder and N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine The mass ratio of amine is 100:800:0.45:0.9:4, and the mixture is stirred and mixed at a stirring speed of 100 r / min and a temperature of 75°C for 40 hours. After the reaction is completed, a mixed solution is obtained, and the mixed solution is electrospun at a spinning voltage of 28 kV, a flow rate of 0.5 mL / h, and a receiving distance of 15 cm. The mixed solution is placed in a vacuum drying oven at 60°C and dried for 12 hours, and rolled at a pressure of 5 MPa for 2 minutes to obtain a modified polyacrylonitrile fiber membrane;

[0113] The thickness of the modified polyacrylonitrile fiber membrane is 50 μm;

[0114] Step 3: Use modified polyacrylonitrile fiber film as the outer film, EPE foam cotton sheet as the middle film, PP non-woven fabric as the inner film, and bond the outer film, the middle film and the inner film with a pressure-sensitive adhesive to obtain a heat-insulating and weather-resistant composite material.

[0115] In the above embodiments and comparative examples, polyacrylonitrile resin was purchased from Hubei Shuaiyan Ligao Biomedicine Co., Ltd., with the model number SYLG-1106 and the molecular weight of 90,000; montmorillonite was purchased from Guangzhou Yifeng Chemical Technology Co., Ltd., with the model number TY-710C and the particle size of 50 nm; silver powder was purchased from Shanghai Yaotian New Materials Technology Co., Ltd., with the model number YT-Ag-04-1 and the average particle size of 50 nm; EPE foam cotton sheet was purchased from Hongbaotai Packaging Industry Co., Ltd. with the thickness of 0.5 mm; PP non-woven fabric was purchased from Hunan Mingyu Non-woven Fabric Co., Ltd. with the model number MYWFB11 and the weight of 50 g / m 2 The pressure-sensitive adhesive was purchased from Yingchuang Technology (Guangdong) Co., Ltd., type: acrylic adhesive, item number: IRW-E027L, solid content: 60%, viscosity: 1200 mPa·s.

[0116] Test example

[0117] The performance tests were performed on the modified polyacrylonitrile fiber membranes prepared in Examples 1-6 and Comparative Examples 1-2:

[0118] (1) Thermal insulation performance: The out-of-plane thermal conductivity of the modified polyacrylonitrile fiber membrane was measured according to the ASTM D5470 standard. The results are shown in Table 1:

[0119] Table 1

[0120]

[0121] As shown in Table 1, the modified polyacrylonitrile fiber film prepared by the present invention has good thermal insulation performance. Montmorillonite has a lamellar thermal insulation effect, and silver powder has a high reflectivity and can reflect heat away. Both have good thermal insulation performance. Montmorillonite and silver powder are connected to N, N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl) hexamethylenediamine molecules through stable chemical bonds. The mutual entanglement between N, N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl) hexamethylenediamine and polyacrylonitrile molecular chains improves the compatibility and dispersion uniformity of montmorillonite and silver powder in the modified polyacrylonitrile spinning solution, and the thermal insulation performance is enhanced. Compared with Example 1, in Comparative Example 2, montmorillonite and silver powder did not chemically bond with N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine, and their compatibility and dispersion uniformity in the modified polyacrylonitrile spinning solution were reduced, the thermal insulation performance was weakened, and the thermal conductivity coefficient was increased.

[0122] (2) Anti-ultraviolet aging performance: The modified polyacrylonitrile fiber film strip sample was irradiated under a 300W high pressure mercury lamp at 25°C for 240 hours with a lamp distance of 5 cm. After irradiation, the tensile properties were tested. The test results are shown in Table 2:

[0123] Table 2

[0124]

[0125] As shown in Table 2, the modified polyacrylonitrile fiber membrane prepared by the present invention has good anti-ultraviolet aging performance. In the preparation process of the modified polyacrylonitrile fiber membrane, by introducing the anti-ultraviolet component 4-propyleneoxy-2-hydroxybenzophenone into polyacrylonitrile, and 4-propyleneoxy-2-hydroxybenzophenone and polyacrylonitrile are connected by a stable chemical bond, the anti-ultraviolet component has high compatibility and uniform dispersion in polyacrylonitrile, and good anti-ultraviolet aging performance. Compared with Example 1, in Comparative Example 1, 4-propyleneoxy-2-hydroxybenzophenone is not connected to the polyacrylonitrile molecular chain by a stable chemical bond, and the anti-ultraviolet aging performance is reduced.

[0126] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a heat-insulating and weather-resistant composite material, characterized in that: The steps include: Step 1, adding polyacrylonitrile resin to N,N-dimethylformamide, stirring until dissolved, adding hexafluorobutyl acrylate, 4-propyleneoxy-2-hydroxybenzophenone and benzoyl peroxide, reacting, and after the reaction is completed, precipitating, filtering, washing, and drying to obtain modified polyacrylonitrile; Step 2: Add modified polyacrylonitrile to N,N-dimethylformamide, stir until dissolved, add epoxy-modified montmorillonite, epoxy-modified silver powder and N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine, continue to react, and after the reaction is completed, obtain a reaction solution, electrospin the reaction solution, dry it, and roll it to obtain a modified polyacrylonitrile fiber membrane; Step 3: Use modified polyacrylonitrile fiber film as the outer film, EPE foam cotton sheet as the middle film, PP non-woven fabric as the inner film, and bond the outer film, the middle film and the inner film with a pressure-sensitive adhesive to obtain a heat-insulating and weather-resistant composite material.

2. The method for preparing a heat-insulating and weather-resistant composite material according to claim 1, characterized in that: In the step 1, the mass ratio of polyacrylonitrile resin, N,N-dimethylformamide, hexafluorobutyl acrylate, 4-propyleneoxy-2-hydroxybenzophenone, and benzoyl peroxide is 100:(800-1000):(2.5-5):(3.5-6):(0.05-0.1).

3. The method for preparing a heat-insulating and weather-resistant composite material according to claim 1, characterized in that: In the step 1, the stirring conditions are stirring at a stirring speed of 100-200 r / min and a temperature of 50-70° C., and the reaction conditions are reacting at a temperature of 80-90° C. for 1.5-2.5 h.

4. The method for preparing a heat-insulating and weather-resistant composite material according to claim 1, characterized in that: In the step 2, the mass ratio of modified polyacrylonitrile, N,N-dimethylformamide, epoxy-modified montmorillonite, epoxy-modified silver powder and N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine is 100:(800-1000):(0.5-1):(1-2):(4-5).

5. The method for preparing a heat-insulating and weather-resistant composite material according to claim 1, characterized in that: In the step 2, the stirring conditions are stirring at a stirring speed of 100-200 r / min and a temperature of 50-70° C., and the conditions for continuing the reaction are stirring at a stirring speed of 100-200 r / min and a temperature of 75-85° C. for 30-40 hours.

6. The method for preparing a heat-insulating and weather-resistant composite material according to claim 1, characterized in that: In the step 2, during electrospinning, the spinning voltage is 28 kV, the flow rate is 0.5 mL / h, and the receiving distance is 15 cm.

7. The method for preparing a heat-insulating and weather-resistant composite material according to claim 1, characterized in that: The epoxy-modified montmorillonite in step 2 is prepared by the following steps: The pH value of the ethanol aqueous solution is adjusted to 3.5-4.5, γ-glycidyloxypropyltrimethoxysilane is added, and after hydrolysis, montmorillonite is added to react, and after the reaction is completed, the reaction is filtered, washed, and dried to obtain epoxy-modified montmorillonite; The mass ratio of the ethanol aqueous solution, γ-glycidyloxypropyltrimethoxysilane and montmorillonite is 100:2.5:(2.5-4), the hydrolysis condition is 3.5-4.5h at a stirring speed of 100-200r / min, and the reaction condition is reflux reaction at a temperature of 65-75°C for 20-30h.

8. The method for preparing a heat-insulating and weather-resistant composite material according to claim 1, characterized in that: The epoxy-modified silver powder in step 2 is prepared by the following steps: The mixed solvent is mixed with γ-glycidyloxypropyltrimethoxysilane, the pH value is adjusted to 4-6, silver powder is added, reacted, and after the reaction is completed, filtered, washed, and dried to obtain epoxy-modified silver powder; The mixed solvent is prepared by mixing ethyl acetate / butyl acetate / cyclohexanone in a mass ratio of 2:1:1, the mass ratio of the mixed solvent, γ-glycidyloxypropyltrimethoxysilane and silver powder is 100:1:(1-2), and the reaction conditions are to react at a temperature of 50-70°C for 8-10h.

9. A heat-insulating and weather-resistant composite material prepared by the method for preparing a heat-insulating and weather-resistant composite material according to any one of claims 1 to 8.

10. Use of the heat-insulating and weather-resistant composite material as claimed in claim 9 in car covers.

Citation Information

Patent Citations

  • Heat-insulating and flame-retardant car cover made of polyurethane layered material and preparation method thereof

    CN117301677B

  • Preparation method for hydrophobic modified silk fiber material

    CN111501341A

  • Car door pushing type automobile sun-shading board

    CN201077347Y

  • Automobile coat

    CN207565297U

  • Air sandwich sunshade heat insulating cover for vehicle

    CN2866221Y